A Jewish Intaglio from Roman Ammaia, Lusitania - Cravinho, G.; Amorai-Stark, S. (Liber Annuus, 2006)
Abstract The article presents a Jewish Menorah intaglio from Roman Ammaia, Lusitania, present day Portugal. It surveys the evidence of other small Jewish artifacts from the Western Diaspora and of the quartz industry in Ammaia and its region. It also surveys the evidence of Jews in the province. We show that the Menorah nicolo, to-date the only Jewish glyptic specimen from this province, is a product of the productive nicolo glyptic workshops in this Roman city, which were part of the regional quartz industry; that this industry which specialized in treated microcystaline quartz but particularly in the manufacture of nicolos was one of the most prolific in the Western Roman empire. Furthermore we prove that as the single secured Jewish gem from Roman Lusitania this intaglio constitutes the most Western glyptic evidence to Jewish presence within the Roman empire. As an important addition to the small number of Jewish gems of secured Western Diaspora provenance depicting the Menorah with its 3 sacred symbols (the Lulav, Etrog and Shofar) this 3rd c. A.D. Jewish intaglio proves the existence of Jews in Ammaia and strengthens former evidence as to the presence of Jewish communities in Lusitania.